A novel structure of YSZ coatings by atmospheric laminar plasma spraying technology. (August 2018) - Liu, Sen-Hui; Li, Cheng-Xin; Zhang, Hui-Yu; Zhang, Shan-Lin; Li, Lu; Xu, Pan; Yang, Guan-Jun; Li, Chang-Jiu
Abstract: A novel structure of yttria stabilized zirconia coatings was developed in this study by a newly laminar plasma spraying technology in atmospheric environment. The unique microstructures of coatings showed the multi-island protrusions feature at the top surface, quasi-columnar structures along the cross-section distributed as a certain interval and hybrid droplet/vapor deposited structures at the fracture surface. The distributions of particle velocity and surface temperature along the axial direction of long laminar plasma jet were investigated and compared with other plasma spraying methods. The effects of different microstructures to thermal conductivities comparing with other current plasma spray methods were also demonstrated. Graphical abstract: Unlabelled Image